Optimasi Parameter Operasi Mesin Air Slip Forming untuk Meminimalkan Cacat Produk - Didik Wahjudi; Amelia Amelia (Institute of Research and Community Outreach, Petra Christian University, 1999)
Air Slip Forming machine is one of the machines that is used to produce luggage. However, so far in the manufacturing process determination of operation parameter air-out time (X1), air-in time (X2) and heating time (X3), also the response variable which is the circumference of the luggage (Y) are done by trial and error. Therefore the circumference of the luggage is not the same as the standard one. Respone surface method and CCD formula will be used to get this mathematical model which describe the relation between luggage circumference and other influential variables. The best condition to produce luggage with circumference that meets the standard are 6.3 sec for air-out time, 2.6 sec for air-in time and 62 sec for heating time. Abstract in Bahasa Indonesia : Mesin Air Slip Forming merupakan salah satu mesin untuk memproduksi koper. Selama ini dalam proses produksinya penentuan parameter operasi waktu air-out (X1), waktu air-in (X2), dan waktu pemanasan (X3) serta variabel respon berupa keliling koper (Y) dilakukan dengan cara trial and error. Karena itu sering didapatkan ukuran keliling koper tidak sesuai standar. Metode respon surface dan rancangan CCD akan digunakan untuk mendapatkan model matematis yang menggambarkan hubungan antara keliling koper dan variabel-variabel yang mempengaruhi. Kondisi proses yang menghasilkan keliling koper yang sesuai standar adalah 6.3 detik untuk waktu air out, 2.6 detik untuk waktu air-in dan 62 detik untuk waktu pemanasan. Kata kunci : permukaan respon, CCD